Prospects of Cultural Heritage Tourism in Panauti, Nepal - Kunwar, Ramesh Raj; Phuyal, Upama (Journal of Tourism & Adventure, 2025)
Panauti, an open-air museum located near the Kathmandu Valley, holds enormous tourism potential rooted in its cultural richness and a longstanding tradition of hospitality. Despite its heritage value, limited scholarly attention has been given to Panauti from a cultural heritage tourism perspective. This paper aims to explore the prospects of cultural heritage tourism in Panauti by examining the tangible and intangible aspects of cultural heritage, the host’s expression of hospitality, and how guests develop a sense of authenticity. It further examines government and local initiatives for protecting cultural heritage and promoting it as a tourist destination. A qualitative research method with an exploratory design was adopted, incorporating interviews, participant observation, and content analysis methods to analyze the topic of study. Key attractions identified around Panauti are temples, traditions, culture, museums, and festivals. Similarly, the homestay, the lifestyle of locals, slow food, and the hospitality culture are appealing to visitors as they enhance the feelings of authenticity. Despite having potential, the slow growth of tourism in Panauti can be attributed to factors such as mismanagement, inadequate facilities, and a lack of effective promotion for domestic tourists. Even though the culture is in the gradual process of transformation, the Newars of Panauti are revitalizing their culture for tourism development. Finding suggests that Panauti is one of the prominent tourism destinations, and strategic promotion could increase the visibility of this place for both domestic and international tourists, leading to sustainable religious and cultural heritage tourism development. This study incorporates an introduction, literature review, methodology, findings, discussions, and conclusion.